Interactions among shrub cover and the soil microclimate may determine future Arctic carbon budgets - Sean M. P. Cahoon; Patrick F. Sullivan; Gaius R. Shaver; Jeffrey M. Welker; Eric Post (Ecology Letters, 2012)
Arctic and Boreal terrestrial ecosystems are important components of the climate system because they contain vast amounts of soil carbon (C). Evidence suggests that deciduous shrubs are increasing in abundance, but the implications for ecosystem C budgets remain uncertain. Using midsummer CO 2 flux data from 21 sites spanning 16° of latitude in the Arctic and Boreal biomes, we show that air temperature explains c . one‐half of the variation in ecosystem respiration ( ER ) and that ER drives the pattern in net ecosystem CO 2 exchange across ecosystems. Woody sites were slightly stronger C sinks compared with herbaceous communities. However, woody sites with warm soils (> 10 °C) were net sources of CO 2 , whereas woody sites with cold soils (